SPECIFIC FEATURES OF LUXURY PRODUCTS BRANDING - Aleksandra Krajnović; Jurica Bosna; Sara Grubišić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
In this modern world characterized by rapid change, the role of marketing is increasingly important. Developing a brand is one way in which a competitive advantage can be achieved. The work defines the concept of luxury through the prism of marketing, shows the specifics of marketing in the luxury products market and the key factors that influence the demand for luxury products. The paper found that the key to success is to effectively create a market strategy whose main goal is to create a strong and emotional long-term relationship between the brand and the consumer. Also, the new trend of "abundant rarity" has led companies in the luxury goods sector to strive to strike an optimal balance between exclusivity and affordability.